Understanding Vocational Business Students Sustainability Consciousness (World Journal of Vocational Education and Training, 2021)
This study aims to investigate the factors influencing vocational business students’ sustainability consciousness. We surveyed 1,007 business students in a vocational college in China. We found that although both formal class learning and informal learning outside the classroom were positively related to students’ sustainability consciousness, formal class learning was more influential than the latter. Female vocational business students tended to have a higher level of sustainability consciousness than male students did. Second-year vocational business students tended to have a higher level of sustainability consciousness than first-year students did. Our study not only contributes to the prior literature but also provides implications for improving sustainability education in vocational colleges.